On Evaluation and Comparison of Blast Loading Methods Used In Numerical Simulations - Vahdet Uçar; Atıl Erdik (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
It is crucial to assess thedynamic behavior of structures exposed to blast loading in order to improve theintegrity and survivability. Numerical simulations are widely used to predictthe response of structures under blast loading. A commercial nonlinear finiteelement code, LS-DYNA provides three blast loading methods: Empirical blastmodeling technique CONWEP, Arbitrary Lagrangian Eulerian technique (ALE), andhybrid CONWEP - ALE technique. In this study, an experimental testing of a flatplate subjected to blast loading is modeled using these three blast loadingmethods in LS-DYNA. Mesh resolution study of ALE formulation is conducted todetermine the influence of element mesh size on predicting blast loadingeffects that is converted through fluid structure interaction algorithm fromEulerian to Lagrangian type of elements. It is drawn a comparison between peakpressures calculated in simulations and maximum dynamic deformation measured inthe field test. Finally, the discussion and conclusion are provided.